2006
DOI: 10.3347/kjp.2006.44.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of experimental animals to reinfection with Clonorchis sinensis

Abstract: The present study observed the resistance to reinfection with Clonorchis sinensis in various experimental animals including mice, guinea pigs, rabbits, and dogs, as well as rats and hamsters. The resistance rates to reinfection in rats, mice, hamsters, guinea pigs, rabbits, and dogs were 79.7%, 58.0%, -12.6%, 54.8%, 62.6%, and 6.0%, respectively. Worms recovered from reinfected rats and mice were immature, and significantly smaller than those from the primarily infected (P < 0.01), whereas those from other ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…The worm recovery rate in re-infected rats in our study was as low as 1%, which is similar to that reported in previous studies Chung et al 2004;Sohn et al 2006). Our study observes that resistance is closely related to the time that has passed since the termination of the primary infection by treatment.…”
Section: Discussionsupporting
confidence: 92%
“…The worm recovery rate in re-infected rats in our study was as low as 1%, which is similar to that reported in previous studies Chung et al 2004;Sohn et al 2006). Our study observes that resistance is closely related to the time that has passed since the termination of the primary infection by treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Semiquantitative measurement of apoptosis showed that livers from rat at 4, 6, 8, 12 weeks postinfection with C. sinensis confirmed the higher apoptotic index compared with normal control (e, p<0.01), similar result was detected in human liver infected with C. sinensis (f, p<0.01) infection (Yoon et al 2001). Rat is also susceptible to C. sinensis and is broadly used as animal model in the study of pathogenesis (Choi et al 2004b;Quan et al 2005;Sohn et al 2006). In the present study, Wistar rats were administered intragastrically with 100 metacercariae of C. sinensis, and then the worm eggs could be detected from the stool in 100% of rats in infected groups 6 weeks postinfection.…”
Section: Discussionsupporting
confidence: 64%
“…Helminth-free inbred Syrian golden hamsters ( Mesocricetus auratus ) were infected with metacercariae of each species as described previously [40], [47]. Hamsters used in this study were maintained at the animal research facilities at the Faculty of Medicine, Khon Kaen University, Thailand and the School of Medicine, Gyeongsang National University, South Korea.…”
Section: Methodsmentioning
confidence: 99%